Disposable pyruvate biosensors for routine assessment of onion flavour - Abayomi, Louise Anike (Cranfield University, 2007)
The UK-grown onion sector shows strong potential for growth through new product development as consumers become increasingly aware of the health and dietary benefits of fresh onion consumption. Prospects for the production of new, more palatable sweet onions will be boosted by the development of improved grower diagnostics for flavour standardisation. Growers require simple-to-use on-farm diagnostics to assure flavour quality. The introduction of pungency tests has led to increased mild onion sales, however currently tests are out-sourced and as a result costly. Through this Defra- (Department for Agriculture Food and Rural Affairs) sponsored research project (HL0164), hand-held biosensor technology, adapted from the medical sector, has been developed for improved and lower cost pungency and sweetness analysis in onions. Cont/d.